New electric power CDN based on the technology of SDN and NFV - Hongkai WANG; Hanyong HAO; Botao YU; Linqing LI (Dianxin kexue)
With the development of smart grid and the increasing of network application within the electric power information network,electric power CDN plays an important role of network acceleration technology,traffic load balancing and network security.However,facing the rapidly changing of application requirements,electric power CDN was required to response to the application deployment quickly and possess flexible application extensibility.In addition,there are some problems on electric power CDN node expansion,such as complex operations management and low utilization rate of resources.It is necessary to reform the traditional power CDN architecture,SDN and NFV technique can support.The data control can be extracted and transmitted by SDN from the network data,so it is conducive to expand a variety of application in power CDN rapidly.And NFV can expand the CDN node capacity and schedule node resources based on the application.It can effectively reduce the capital ecpenditure,storage and power consumption.